Complications of synthetic mesh inserted for stress urinary incontinence. (15th October 2020) - Morton, Simon; Wilczek, Yasmine; Harding, Christopher
Abstract : Objective: To provide an update on the literature regarding the management of complications secondary to synthetic mesh placed to treat stress urinary incontinence (SUI). Methods: We performed a systematic review of the literature using a multi‐database structured search within OVID, the Medical Literature Analysis and Retrieval System Online (MEDLINE), the Excerpta Medica dataBASE (EMBASE) and Cochrane library databases; using the keywords: urology, incontinence, mesh and surgery. Results: Several million synthetic polypropylene meshes have been inserted into women worldwide to manage SUI. Unfortunately, a significant number of women have now reported life‐changing complications. We found a paucity of studies, heterogeneity of cohorts, poor long‐term follow‐up, and lack of evidence on the effective management of mesh‐related complications. Conclusions: The contemporary evidence is low‐level and often contradictory, which prevents robust recommendations regarding treatment. A prospective registry will be required to generate meaningful outcome data and help in the complex management of patients who have mesh‐related complications.